Identification and characterization of chitinolytic bacteria from beetle larvae gut and seawater samples / A’isyah Nabila Idris - A’isyah Nabila , Idris (2018)
An abundant amount of chitin could be found in the world and most of them are disposed as waste and cause a major problem in industry. Chitin flakes are mainly derived from shellfish such as crab and shrimp that could be converted into useful product that can benefit human and reduce problems for environment. Several steps including isolation of chitinolytic bacteria, purification of chitinase and the performance of the purified chitinase in various conditions were done throughout this study. Chitinolytic bacteria produce enzymes that help in chitin degradation and it can be isolated from several sources. In this study, the chitinase producing bacteria were locally isolated from rhinoceros beetle (Oryctes rhinoceros) larvae gut found in mushroom compost, and from seawater, collected at Beras Basah Island, Langkawi. Two samples were selected from these two sources and labelled as RBLG1 and BBL1. Both samples were identified using 16s rDNA sequencing. Both identified strains have a strong homology to Bacillus cereus. Chitinases that produced from both strains then undergo purification process using ammonium sulphate precipitation, ion exchange chromatography and gel filtration process. The purified chitinase from RBLG1 shows the homogeneity 1.9 fold while homogeneity of purified chitinase from BBL1 was 2.78 fold after gel filtration process. The purified chitinases were identified and analyzed using SDS-PAGE and the molecular mass from both strains was approximately 40 kDa. Then, several characterization studies such as effect of various temperatures, pHs, substrate concentrations and also metal ion were done using purified enzymes. Enzyme from RBLG1 shows highest chitinase activity at pH 4 (0.0330 U/mL) and 60°C (0.0354 U/mL), while chitinase from BBL1 shows highest enzymatic activity at pH 6 (0.0360 U/mL) and 45°C (0.0367 U/mL). The maximum activities for both strain RBLG and BBL1 were 0.0341 U/ml and 0.0346 U/ml respectively at 1.5% substrate concentration at 37°C. For metal ion test, chitinase from RBLG1 shows lowest enzymatic activity when chitinase incorporated with Zn+, while chitinase from BBL1 shows lowest enzymatic activity when chitinase incorporated with K+. Lastly, study on kinetic performance for chitinase using Michaelis-Menten equation from RBLG1 shows Km and Vmax values were 0.5093 g/L and 0.0066 [P] (g/L/min) respectively meanwhile for chitinase from BBL1, the Km and Vmax were 0.3887 g/L and 0.0080 [P] (g/L/min) respectively.